Airway mucin MUC5AC and MUC5B concentrations and the initiation and progression of chronic obstructive pulmonary disease: an analysis of the SPIROMICS cohort. Issue 11 (November 2021) - Radicioni, Giorgia; Ceppe, Agathe; Ford, Amina A; Alexis, Neil E; Barr, R Graham; Bleecker, Eugene R; Christenson, Stephanie A; Cooper, Christopher B; Han, MeiLan K; Hansel, Nadia N; Hastie, Annette T; Hoffman, Eric A; et al.
Summary: Background: We previously described the contributions of increased total airway mucin concentrations to the pathogenesis and diagnosis of the chronic bronchitic component of chronic obstructive pulmonary disease (COPD). Here, we investigated the relative contribution of each of the major airway gel-forming mucins, MUC5AC and MUC5B, to the initiation, progression, and early diagnosis of airways disease in COPD. Methods: SPIROMICS was a multicentre, observational study in patients aged 40–80 years recruited from six clinical sites and additional subsites in the USA. In this analysis, MUC5AC and MUC5B were quantitated by stable isotope-labelled mass spectrometry in induced sputum samples from healthy never-smokers, ever-smokers at risk for COPD, and ever-smokers with COPD. Participants were extensively characterised using results from questionnaires, such as the COPD assessment test (CAT) and St George's Respiratory Questionnaire; quantitative CT, such as residual volume/total lung capacity ratio (RV/TLC) and parametric response mapping-functional small airway disease (PRM-fSAD); and pulmonary function tests, such as FEV1, forced vital capacity (FVC), and forced expiratory flow, midexpiratory phase (FEF25–75% ). Absolute concentrations of both MUC5AC and MUC5B were related to cross-sectional (baseline, initial visit) and 3-year follow-up longitudinal data, including lung function, small airways obstruction, prospective acute exacerbations, and smoking status as primary outcomes. This study is registered with ClinicalTrials.gov (NCT01969344 ). Findings: This analysis included 331 participants (mean age 63 years [SEM 9·40]), of whom 40 were healthy never-smokers, 90 were at-risk ever-smokers, and 201 were ever-smokers with COPD. Increased MUC5AC concentrations were more reliably associated with manifestations of COPD than were MUC5B concentrations, including decreased FEV1 and FEF25–75%, and increased prospective exacerbation frequency, RV/TLC, PRM-fSAD, and COPD assessment scores. MUC5AC concentrations were more reactive to cigarette smoke exposure than were MUC5B concentrations. Longitudinal data from 3-year follow-up visits generated a multivariate-adjusted odds ratio for two or more exacerbations of 1·24 (95% CI 1·04–1·47, p=0·015) for individuals with high baseline MUC5AC concentration. Increased MUC5AC, but not MUC5B, concentration at baseline was a significant predictor of FEV1, FEV1 /FVC, FEF25–75%, and CAT score decline during the 3-year follow-up. Moreover, current smokers in the at-risk group showed raised MUC5AC concentrations at initial visits and decreased lung function over 3 years. By contrast, former smokers in the at-risk group showed normal MUC5AC concentrations at the initial visit and preserved lung function over 3 years. Interpretation: These data indicate that increased MUC5AC concentration in the airways might contribute to COPD initiation, progression, exacerbation risk, and overall pathogenesis. Compared with MUC5B, greater relative changes in MUC5AC concentrations were observed as a function of COPD severity, and MUC5AC concentration seems to be an objective biomarker to detect disease in at-risk and pre-COPD individuals. These data suggest that MUC5AC-producing pathways could be potential targets for future therapeutic strategies. Thus, MUC5AC could be a novel biomarker for COPD prognosis and for testing the efficacy of therapeutic agents. Funding: National Institutes of Health; National Heart, Lung, and Blood Institute.